Diversitas dan sebaran kumbang staphylinid di lahan pertanaman padi (Oryza sativa L.) dan ubi jalar (Ipomoea batatas L.) - Tri Atmowidi; Taruni Sri Prawasti; Dimas Adjie Prasetyo; Annisa Sendekia Lubis; Nofialdi Nofialdi; Sefriatin Nurmaulani (Perhimpunan Entomologi Indonesia, 2016)
Staphylinid beetle (Coleoptera) is characterized by short elytra with orange, brown, or black body color. The objective of this research was to analyse diversity of staphylinid beetles in paddy and sweet potato fields and distribution of the species in sweet potato field. Collections of beetle were done by using road sampling method in two types of agricultural fields. Distribution of beetle population were observed in the plots (1 m x 1 m) placed systematically. Seven species of staphylinids were found in this research. Five species (Paederus fuscipes Curtis, Stenus sp., Astenus sp., Hypostenus sp., and Cryptobium abdominale Motsch.) were found in paddy fields. We also found five species of staphylinid beetles (P. fuscipes, Medon sp., Stenus sp., Hypostenus prahoeensis Benick, and Philonthus sp.) in sweet potato fileds. In paddy and sweet potato fileds were dominated by P. fuscipes. Diversity of staphylinid in paddy and sweet potato fields were low. In sweet potato fields, P. fuscipes showed highest important value index (115.98%), followed by Stenus sp. (69.35%), and H. prahoeensis (5.65%). and Population distribution of P. fuscipes, Medon sp., Stenus sp., dan Philonthus sp. were uniform, while H. prahoeensis was clump.